フジ コウロ 1975 1976 ニオケル ヒョウメン カイスイチュウ ノ クロロフィル リョウ - 大山, 佳邦; オオヤマ, ヨシクニ; 間山, 力; マヤマ, ツトム; OHYAMA, Yoshikuni; MAYAMA, Tsutomu (国立極地研究所, 1976)
P(論文) 1975年11月から1976年4月まで,第17次南極地域観測隊の海洋生物観測の一環として,「ふじ」の航路に沿って表面海水中のクロロフィル-α量の測定を行った,クロロフィル-α量はプリンスオラフ海岸沖のパック・アイス中で最も高い値(2.49mg/m^3)が得られた.その他の海域では亜南極帯,マカッサール海峡,マラッカ海峡で高い値(0.4-0.9mg/m^3)を示した.今回は昭和基地沖の氷縁を離れてから最初の寄港地が,従来のケープタウンからモーリシャスのポートルイスに変更された.このため従来観測されなかった海域でのクロロフィル-α量を測定することができた. During the relief voyage of FUJI to Syowa Station, Antarctica, from November 1975 to April 1976, the chlorophyll contents in surface water were measured twice a day as a routine shipboard oceanographic observation. The distribution of chlorophyll contents during the cruise did not show a marked difference from the past years. The maximum value (2.49mg/m^3) was recorded in the pack-ice region in the Antarctic Ocean off Prince Olav Coast. High values more than 0.4mg/m^3 were observed in such region as the Makassar Strait, Sub-Antarctic sea and the Malacca Strait. After leaving the ice edge off Syowa Station, the vessel sailed up to the north along about 33.5°E which is far east compared with the course of the previous voyages, which added new data in the series of chlorophyll observation. departmental bulletin paper